2019
DOI: 10.1002/chem.201901784
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Catalytic [4+1]‐Cyclization of ortho‐Hydroxy‐para‐Quinone Methides with Allenoates

Abstract: The first highly asymmetric catalytic synthesis of densely functionalized dihydrobenzofurans is reported, which starts from ortho ‐hydroxy‐containing para ‐quinone methides. The reaction relies on an unprecedented formal [4+1]‐annulation of these quinone methides with allenoates in the presence of a commercially available chiral phosphine catalyst. The chiral dihydrobenzofurans were obtained as single diastereomers in yields up to 90 % and with enantiomeric ratios … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 61 publications
(38 reference statements)
0
21
0
Order By: Relevance
“…Wang and co-workers accomplished a chiral bifunctional phosphonium salt (25) catalyzed highly enantio-and diastereo-selective [4 + 1]-annulation of 2-hydroxyphenyl-substituted p-QMs (16) with α-halogenated ketones (23) to obtain enantiomerically pure 2,3-dihydrobenzofuran derivatives (24) [Scheme 5]. [22] The control experiments suggested that, the p-QM ( 16) initially undergoes a base-mediated nucleophilic substitution reaction with 23 to produce 26, which, under the influence of the chiral catalyst 25, undergoes an enantioselective intramolecular 1,6-conjugate reaction to generate the desired product 24 with excellent enantioselectivities.…”
Section: Synthesis Of Dihydrobenzofuransmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang and co-workers accomplished a chiral bifunctional phosphonium salt (25) catalyzed highly enantio-and diastereo-selective [4 + 1]-annulation of 2-hydroxyphenyl-substituted p-QMs (16) with α-halogenated ketones (23) to obtain enantiomerically pure 2,3-dihydrobenzofuran derivatives (24) [Scheme 5]. [22] The control experiments suggested that, the p-QM ( 16) initially undergoes a base-mediated nucleophilic substitution reaction with 23 to produce 26, which, under the influence of the chiral catalyst 25, undergoes an enantioselective intramolecular 1,6-conjugate reaction to generate the desired product 24 with excellent enantioselectivities.…”
Section: Synthesis Of Dihydrobenzofuransmentioning
confidence: 99%
“…A fascinating organocatalytic protocol, based on phosphine catalysis, has been reported by Waser and co-workers to access enantiomerically-enriched dihydrobenzofurans (31) from 16 and allenoate (30) [Scheme 7]. [24] Waser's approach basically involves the activation of 30 by a chiral phosphine catalyst followed by a highly enantioselective 1,6-conjugate addition reaction of 32 with 16 to generate the zwitterionic intermediate 33. This intermediate 33, afterwards experiences a series of proton transfers and, then finally, undergoes an intramolecular cyclization to form the product 31 along with the phosphine catalyst.…”
Section: Synthesis Of Dihydrobenzofuransmentioning
confidence: 99%
“…Very recently, an asymmetric (4 + 1) annulation of ortho ‐hydroxy‐ para ‐quinone methides 42 with α‐substituted allenoates was further developed by the same group. By employing a commercially available chiral spiro phosphine catalyst 44 and in the presence of two equivalents K 2 CO 3 , the (4 + 1) annulation reaction smoothly afforded the corresponding dihydrobenzofurans 43 in moderate to high yields with exclusive diastereoselectivity and high enantiomeric ratio (Scheme ) …”
Section: (4 + 1) Annulation Reactions Of Allenoatesmentioning
confidence: 99%
“…48 In 2019, Waser and co-workers started from o-hydroxyphenyl-substituted p-quinone methides in an asymmetric catalytic synthesis of highly functionalized DHBs. 49 The reaction relied on a formal [4+1]-annulation of these quinone methides with allenoates in the presence of a commercially available chiral phosphine catalyst. Chiral DHBs were obtained as single diastereomers up to 84% yield and with up to 95:5 er…”
Section: P-quinone Methides and P-quinonesmentioning
confidence: 99%